Analisis Pengaruh Tax Administration Services dan Penalty Rate terhadap Kepatuhan Wajib Pajak UMKM Tanjung Priok - Wa Ode Nurul Fatma; Udin Saepudin; Sopian Sopian (BADAN PENERBIT STIEPARI PRESS, 2025)
This study aims to analyze the influence of tax administration services and the level of tax sanctions on taxpayer compliance of Micro, Small, and Medium Enterprises (MSMEs) in Tanjung Priok District. The background of this study is based on the low level of tax compliance in the MSME sector, even though this sector makes a significant contribution to the gross domestic product (GDP). The study used a quantitative approach with a survey method by distributing questionnaires to 99 MSME respondents. Data were analyzed using multiple linear regression to test the relationship between variables. The results showed that tax administration services have a positive and significant influence on taxpayer compliance, as indicated by a regression coefficient of 0.287. This means that the better the administrative services provided, the higher the level of tax compliance. In addition, tax sanctions also showed a positive and significant influence on compliance, with a regression coefficient of 0.197. This indicates that the implementation of strict and consistent sanctions can encourage taxpayers to fulfill their tax obligations. Simultaneously, these two independent variables have a significant influence on taxpayer compliance. Thus, improving the quality of tax administration services and the enforcement of strict and fair sanctions are crucial in increasing tax compliance among MSMEs. This study recommends the need to increase tax education and outreach to MSMEs so that they better understand their tax rights and obligations comprehensively.